A Leadership Capability Framework for South African Higher Education - Michael Stanley Cloete; Sonja Grobler (Journal of Ethics in Higher Education)
Rapid changes in economy, society, technology, and politics, alongside reduced subsidies, curriculum decolonisation, and Covid-19 disruptions, challenge South African Higher Education Institutions (HEIs). This study examines leadership capabilities needed to navigate these complexities, identifying flexibility, collaboration, visionary thinking, and ambiguity tolerance as key to fostering innovation and sustainability. It offers a model for effective leadership in South African HEIs and other dynamic sectors.